Do endoflip assessments of anal sphincter distensibility provide more information on patients with fecal incontinence than high‐resolution anal manometry?. Issue 3 (15th December 2015) - Gourcerol, G.; Granier, S.; Bridoux, V.; Menard, J. F.; Ducrotté, P.; Leroi, A. M.
Abstract: Background: Anal manometry is the standard technique for evaluating anal sphincter function. However, the functional lumen imaging probe (EndoFLIP ® ) can be used to measure sphincter distensibility during volume‐controlled distensions. Our aims were (i) to assess anal distensibility in patients with fecal incontinence (FI) and in healthy subjects using the EndoFLIP ® and (ii) to compare the results with anal pressures measured by 3D high‐resolution manometry (3D‐HRM) to determine whether the EndoFLIP ® was more sensitive and specific for diagnosing FI than 3D‐HRM. Methods: EndoFLIP ® and 3D‐HRM assessments of 34 female FI patients and 40 healthy female subjects were performed. Anal distensibility was measured as the median cross‐sectional area at the narrowest point divided by the corresponding intra‐bag pressure at rest and during peak voluntary contraction and was expressed in mm 2 /mmHg. Key Results: A 40‐mL anal distensibility index was selected for further comparisons as it provided the best discrimination between the FI patients and the healthy subjects. The index was significantly higher in the FI patients than in the healthy subjects at rest ( p = 1.10 −4 ) and during voluntary contraction ( p = 1.10 −4 ). The index at rest and during voluntary contraction appeared to be more appropriate than anal pressures for discriminating between FI patients and healthy subjects. Conclusions & Inferences: The present study confirmed that FI is associated with an abnormally high distensibility index at rest and during voluntary contraction. The ability of the distensibility index to discriminate between FI patients and healthy subjects was significantly better than anal pressure. Abstract : The EndoFLIP ® can be used to measure anal canal distensibility. Fecal incontinence (FI) is associated with high distensibility at rest and during voluntary contraction. The ability of the distensibility index to discriminate between the FI patients and the healthy subjects was significantly better than anal pressures measured by 3D high‐resolution manometry (3D‐HRM).